1980
DOI: 10.1111/1523-1747.ep12514597
|View full text |Cite
|
Sign up to set email alerts
|

PUVA-induced Repigmentation of Vitiligo: Scanning Electron Microscopy of Hair Follicles

Abstract: PUVA-i-duced repigmentation of vitiligo was studied using both the split-dopa reaction and scanning electron microscopy. Proliferation of hypertrophic, Dopa-positive melanocytes were observed in the lower portion of some hair follicles, whereas other giant melanocytes were observed along the middle portion. The existence of a melanocyte reservoir in human hair follicles is postulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 5 publications
2
73
1
1
Order By: Relevance
“…6 Interestingly, RCM detected some of these melanocytes in hair follicles, the previously described follicular ''reservoir'' of vitiligo. 7 The present study does not indicate the origin of melanocytes for repigmentation process in vitiligo, but it suggests that a time-course RCM study during phototherapy of vitiligo lesions could clarify this question.…”
Section: Ausiliacontrasting
confidence: 61%
“…6 Interestingly, RCM detected some of these melanocytes in hair follicles, the previously described follicular ''reservoir'' of vitiligo. 7 The present study does not indicate the origin of melanocytes for repigmentation process in vitiligo, but it suggests that a time-course RCM study during phototherapy of vitiligo lesions could clarify this question.…”
Section: Ausiliacontrasting
confidence: 61%
“…During the repigmentation of vitiliginous skin, it is thought that MPs become activated, migrate along the basement membrane under the ORS into depigmented skin and then differentiate into mature melanocytes. 2,7) The major structural proteins of the basement membrane zone (BMZ) of both normal skin and hair follicles are type IV collagen (CIV), laminin (LN) and entactin. Fibronectin (FN) present in the BMZ located under the cells of the ORS is not a normal epidermal BMZ component.…”
mentioning
confidence: 99%
“…41 Ortonne et al postulated the existence of a melanocyte reservoir, specifically located in the lower portion of human hair follicles and they proposed that repigmentation of vitiligo was derived from the melanocyte reservoir in the hair follicles. 42 Cui et al confirmed that during vitiligo repigmentation, the number of inactive melanocytes in the outer sheath of the hair follicle increases significantly and some active melanocytes appear in the outer root sheath, hair follicle orifices, and around the perifollicular epidermis. 43 Repigmentation in vitiligo usually begins in the perifollicular area in almost all the cases on treatment.…”
Section: Follicular Graftingmentioning
confidence: 94%